Red palm weevil olfactory proteins annotated from the rostrum provide insights into the essential role in chemosensation and chemoreception - Venthur, Herbert; Arias, Ignacio; Lizana, Paula; Jakše, Jernej; Alharbi, Hatten A.; Alsaleh, Mohammed Ali; Pain, Arnab; Antony, Binu (Frontiers in Ecology and Evolution, 2023)
Red palm weevil (RPW), Rhynchophorus ferrugineus (Coleoptera: Curculionidae), is rapidly infesting palm trees (Arecaceae) in several countries, threatening coconut, date, and oil cultivations. The male-produced aggregation pheromone in palm weevils has been reported to be secreted through the mouth to the rostrum, a snout-like projection key for pheromone emission and dispersion.The olfactory mechanisms that underlie peripheral odorant detection in RPW have been addressed at the antennal level. However, the rostrum remains unexplored. Through RNA-seq, 27 odorant-binding proteins (OBPs), 6 chemosensory proteins (CSPs), 4 sensory neuron membrane proteins (SNMPs), 21 gustatory receptors (GRs), 25 odorant receptors (ORs) (including one odorant receptor coreceptor, Orco) and 10 ionotropic receptors (IRs), were identified. We reported 27 novel rostrum-specific olfactory proteins (4 IRs, 11GRs, 2 CSPs, 3 OBPs, and 7 ORs) in R. ferrugineus (Rfer). The OBPs (RferSOBPs) [Rfer with "S" indicating "snout" (rostrum)] were the most abundant transcripts compared with the rest of the olfactory proteins. We identified several rostrum OBPs, which predominately emerged through gene duplication, and were found expressed in both rostrum and antennae. Noticeably, we found R. ferrugineus pheromone-binding protein (RferOBP1768) paralog in the rostrum (RferOBP14) and mapped it in the same scaffold at a different position on the RPW genome as a recent duplicate. We found that an OR (RferSOR1) was the most abundant for both fieldcollected and lab-reared RPWs, in the rostrum and antennae. Likewise, up-regulated olfactory-related proteins were established in field conditions compared with those from laboratory-reared. We found a rostrum-specific, highly expressing RferSIR1 in IR93aclade related to hygrosensation. The role of these olfactory proteins as targets for identifying more specific and powerful semiochemicals is discussed in the context of pest management.